Ácido 3-metilbutanóico e ácido 2-metilbuanóico emitidos por Bacillus spp. inibem o crescimento de (Colletotrichum lindemuthianum) - Faria, Amanda Flausino de (2018)
The management control most used to anthracnose in common bean are related to the use of resistant cultivars and fungicides. However, when the practices are applied individually, they exert selection pressure and may cause the resistance of the cultivars to be broken. In view of this problem, it is necessary to develop alternative control measures for the management of this disease. The antimicrobial activity of the COVs, has been proven in several in vitro studies, showing effect under different pathogens. In this context, the use of the molecules produced by rhizobacteria, may become a promising technique for the control of Colletotrichum lindemuthianum. The objective of this study was to evaluate in vivo the volatile molecules emitted by Bacillus amylolicefaciens ALB629 and UFLA285 against Colletotrichum lindemuthianum, as well as to identify the molecules by solid phase microextraction (SPME) coupled to gas chromatography with mass spectrometry detection (GC-MS), as well as to evaluate the in vitro effect of the molecules identified. The in vivo assay was performed with cv. (Pérola) in pots covered with plastic bags. The plants were exposed to volatile molecules for 72 h, later Colletotrichum lindemuthianum suspension was applied to the aerial part of the plants, evaluated weekly for the severity of the disease, according to Godoy's scale. The identification of the volatiles was performed from the bacteria by SPME-GC / MS. In vitro assays were performed on overlapping plates. In the first assay, the C. lindemuthianum mycelial disc was added simultaneously to 10 μL of each individual pure molecule and in double and triple combination on filter paper disk, inserted at the opposite apex of the plaque to the pathogen. Mycelial development was evaluated at 11 days after plating. In th e second, C. lindemuthianum was grown in Potato dextrose agar medium at 21 ° C for 4 days. On the fourth day the diameter of the pathogen was measured and 10 μL of each individual pure molecule was added and in combination of two and two and triple. Daily, the mycelial growth of the pathogen was evaluated until 7 (dap). The results found in the in vivo test reduced in (79-85%) the severity of Anthracnose in respectively. SPME-GC/MS identified the molecules, 3-hydroxy-2-butanone, 3-methylbutanoic acid and 2-methylbutanoic acid. Inhibition of fungal growth for all treatments over 11 (DAP), except for 3-hydroxy-2-butanone, when evaluated individually, was observed. However, 3-methylbutanoic acid and 2-methylbutanoic acid, alone or in combination, showed up to 94% and 71% control, respectively. Result also found in the positive control B. amylolicefaciens 629, inhibition of 93% in the first assay and 63%. The molecules with direct toxic activity to C. lindemuthianum and with potential ability to control anthracnose in common bean will represent a new option of disease management, for example, to eradicate the pathogen associated with the seed in a purge form.